Biocatalytic transformation of Ganoderma lucidum by porcine pancreatic lipase in hydrophobic deep eutectic solvents - Syed Putra, Sharifah Shahira; Alias, Yatimah; Basirun, Wan Jefrey; Ibrahim, Mastura; Elgharbawy, Amal A.M.; Tola, Hasna; Hayyan, Adeeb; Hashim, Mohd Ali (Elsevier, 2026)
Enzyme applications in industry are often limited by low stability, poor reusability and challenging recovery. This study presents a sustainable strategy for enhancing enzyme performance by immobilizing porcine pancreatic lipase (PPL) onto Ganoderma lucidum using a hydrophobic deep eutectic solvent (HDES) as a reaction medium to facilitate enzyme immobilization. Among several HDESs tested, menthol: decanoic acid (HDES 1) showed the highest lipase activity (198.38%) and was selected for immobilization. Under optimized conditions (3 h, 40 °C, pH 7.0), the immobilized PPL achieved 212.41% catalytic efficiency, a 13 day half-life and retained activity over two reuse cycles. FTIR analysis revealed a shift in the secondary amide band from 3312 to 3306 cm−1, indicating modifications in protein hydrogen bonding. BET and EDX analyses confirmed enzyme adsorption and successful loading, while GC–MS identified fatty acid derivatives, demonstrating effective catalysis. Notably, HDES 1 enabled the immobilized enzyme to replace hexane in esterification reactions, achieving ∼90% fatty acid conversion surpassing the free enzyme. Molecular docking further highlighted strong interactions between HDES 1 and PPL's catalytic residues, validating its stabilizing role. Overall, the G. lucidum-HDES 1 platform provides a green, efficient and versatile biocatalytic system with significant potential for bioenergy production and sustainable applications in the oil industry.